Embedding professional development within the curriculum of graduate programs: An impact survey from biomedical departments in a faculty of medicine - Helen Miliotis; Nana Hyung-Ran Lee; Rachael Cayley; Christina Zakala; Allan Kaplan; Reinhart Reithmeier (PLoS ONE, 2025)
Although the career pathways of biomedical PhDs are increasingly diverse, graduate education continues to rely upon an apprenticeship model, whereby supervisors train the next generation of researchers. To broaden the core competency skills for research productivity and career development across the Temerty Faculty of Medicine’s departments and institutes, a for-credit curricular Graduate Professional Development (GPD) course has been implemented as an integral part of the graduate curriculum in multiple departments. We used three key principles to advance this integrated professional development curriculum: i) a train-the-trainers method for implementation, ii) direct student engagement via a students-as-partners model, one-on-one consultations and videos, and iii) a faculty development program. While programming of this sort has direct benefits, less is known about how students themselves experience curricular GPD. To address the gap in understanding the impact, research was undertaken to inquire about students’ perceived skills development and attitudes towards career choices after taking the GPD course. According to our findings, students see the curricular GPD course as a valuable complement to their graduate education and feel more prepared for their next steps in their career exploration. With buy-in from students, faculty and academic leaders, embedded curricular GPD has transformed the academic culture of graduate education in our faculty, helping our students with skills that empower them to be prepared for their own career development to meet the competitive career realities of our time.